2020
DOI: 10.3390/vibration3040025
|View full text |Cite
|
Sign up to set email alerts
|

Jerk within the Context of Science and Engineering—A Systematic Review

Abstract: Rapid changes in forces and the resulting changes in acceleration, jerk and higher order derivatives can have undesired consequences beyond the effect of the forces themselves. Jerk can cause injuries in humans and racing animals and induce fatigue cracks in metals and other materials, which may ultimately lead to structure failures. This is a reason that it is used within standards for limits states. Examples of standards which use jerk include amusement rides and lifts. Despite its use in standards and many … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 142 publications
0
14
0
Order By: Relevance
“…This beat synchronization was better characterized by the jerk (derivative of acceleration) than by the acceleration ( Fig. 1C ) ( 24 , 25 ). Our experiments in humans also confirmed that the head jerk captured beat synchronization consistently as video motion analyses did (movie S3 and figs.…”
Section: Resultsmentioning
confidence: 94%
“…This beat synchronization was better characterized by the jerk (derivative of acceleration) than by the acceleration ( Fig. 1C ) ( 24 , 25 ). Our experiments in humans also confirmed that the head jerk captured beat synchronization consistently as video motion analyses did (movie S3 and figs.…”
Section: Resultsmentioning
confidence: 94%
“…The rate of change of force is experienced as shock and impact on the trampolinist's body. It is represented by jerk [40][41][42], which is also the rate of change of acceleration.…”
Section: Trampolinist Force Safety Discussionmentioning
confidence: 99%
“…Besides that, acceleration feedback can be a requirement for systems with considerable mass imbalance (Acevedo et al, 2020) or even in the case of a singular mass matrix (Abdelaziz, 2015). Infinite eigenstructures imply very high acceleration or jerk impulses that can cause injuries in humans or animals, see for instance Hayati et al (2020). Then, regularizing the mass matrix via acceleration feedback is often a need.…”
Section: Introductionmentioning
confidence: 99%
“…The control of systems that exhibit vibratory behavior has received increased attention in the last decades. Nowadays, the active or semi-active control of such systems is widely applied from skyscraper stabilization under wind gusts to small applications such as microelectromechanical accelerometers, jerk control, flexible structures of aircraft, and the active suspension of vehicles or seats (Alfadhli et al, 2018; Hayati et al, 2020; Singh et al, 2019). In these problems, the success of the designed system depends upon a series of requirements, for instance, the robustness of the controlled system against a model mismatch, disturbance rejection in track control problems, and saturation avoidance of the control effort.…”
Section: Introductionmentioning
confidence: 99%